2022
DOI: 10.3390/en15238797
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Negative Sequence Voltage Subharmonics on Cage Induction Motors

Abstract: In some power systems, voltage waveforms contain, apart from harmonics, interharmonics and subharmonics that are components of frequency less than or not an integer multiple of the fundamental frequency. Voltage subharmonics and interharmonics may be of both a positive and negative sequence, independently of their frequency. Previous papers on induction motors under subharmonics have been generally limited to the components of a positive sequence. This study deals with the effect of negative sequence subharmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…However, it has been demonstrated that the inertia properties of the machine and the load do influence the generation of undesired disturbances, including torque pulsations, currents and vibrations, especially in the positive sequence, under the influence of interharmonic and subharmonic voltage effects in induction motors [32,33,63,64]. In this scenario, a load with a negligible moment of inertia (NMI) that is lower than the motor's moment of inertia generates larger disturbances [33].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been demonstrated that the inertia properties of the machine and the load do influence the generation of undesired disturbances, including torque pulsations, currents and vibrations, especially in the positive sequence, under the influence of interharmonic and subharmonic voltage effects in induction motors [32,33,63,64]. In this scenario, a load with a negligible moment of inertia (NMI) that is lower than the motor's moment of inertia generates larger disturbances [33].…”
Section: Introductionmentioning
confidence: 99%